Infant Crying and Risk of Hyperactivity and Learning Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Infants with persistent crying (PC) in the first 6 months (mean age 3.8 months) were reassessed at 8 to 10 years of age and compared with 64 classroom controls for hyperactivity, conduct problems and academic difficulties in a prospective study at the University of Hertfordshire, UK.